Political Economy of Institutions, Democracy and Voting - Schofield, Norman.; Schofield, Norman.; Caballero, Gonzalo.; Caballero, Gonzalo. (Springer Berlin Heidelberg : Imprint: Springer, 2011)
This book presents the latest research  in the field of Political Economy, dealing with the integration of economics and politics and the way institutions affect social decisions. The authors are eminent scholars from the U.S., Canada, Britain, Spain, Italy, Mexico and the Philippines. Many of them have been influenced by Nobel laureate Douglass North, who pioneered the new institutional social sciences, or by William H. Riker who contributed to the field of positive political theory. The book focuses on topics such as: case studies in institutional analysis; research on war and the formation of states; the analysis of corruption; new techniques for analyzing elections, involving game theory and empirical methods; comparing elections under plurality and proportional rule, and in developed and new democracies.  .